Psychosocial challenges among gifted underachievers in Ibadan (2014)
One of the biggest problems facing educators is that of student underachievement. Teachers and parents feel confused, frustrated, and disappointed when students fail to realize their potential. Underachievement is not only a problem, but a symptom of problems. To address this, educators must explore factors contributing to underachievement. These factors can be categorized as socio-psychological, family- related, peer-related and school-related. One or all of these factors can hinder student achievement. Teachers, counsellors and families must join in partnerships to best identify and help gifted underachieving students. All the aforementioned points have been well articulated in this study. Another important point that has been captured in this study is the issue of challenges facing the gifted children and some steps one can take to manage them. Those challenges include self-esteem issues, guilt, perfectionism, self- control issues, unrealistic expectations, impatience, friendship, attention and organization issues and burnout. Counselling implications and recommendations were finally stated.